Pengaruh Pemberian Air Kelapa dan Tipe Sambungan terhadap Keberhasilan Sambung Pucuk Durian (Durio zibethinus M.) - Ika Trisna Yanti; Sulandjari Sulandjari; Endang Yuniastuti (Agrosains : Jurnal Penelitian Agronomi, 2013)
Durian is a tropical native fruit from Indonesia with a distinctive flavor. Durian can be propagated durian generatively and vegetatively. Generative propagation of durian can be done by germinating seeds, which is vegetative propagation can be done by top grafting. Top grafting can be accelerated by the addition of plant growth regulators. Growth regulating substances in coconut water complex compounds are useful in differentiating cells. This study aimed to determine the effect of various concentrations of coconut water and the best type of grafting for the success of durian tops grafting. In this study was conducted in horticultural breeding centers Ranukitri Mojogedang Karanganyar April to September 2012. This research used Completely Randomized Design (CRD), which consisted of 2 types of treatment that top grafting, namely: cleft grafting, slash grafting, side grafting and coconut water concentration with 5 levels: 0%, 25%, 50%, 75%, 100% with 5 replications, so that the total treatment was 75. The results showed that the type of cleft grafting was the best grafting type to be used for the success of top grafting compared with other grafting types. Treating coconut water with a concentration of 25% was able to optimize the growth of durian top grafting than other concentrations.